EGFR signalling pathway mutations in colorectal cancer: experience from a new laboratory - Abdul Halim, Sarah; A.Talib, Norlelawati; Ahmad Affandi, Khairunisa; Ismail, Irnani (Academy of Medicine Malaysia, 2023)
Introduction: The evaluation of epidermal growth factor receptor (EGFR) signalling pathway gene mutations such as NRAS, KRAS, BRAF V600E, PIK3CA and AKT1 is decisive in the era of targeted therapy for in colorectal cancer. The aim of this study is to determine the prevalence of these mutations and to categorise the mutation profiles in our local patient cohort.